Size effect in gas forming a hot-bent AA5xxx V-shaped trough trimmed for an airplane strakelet skin panel. Issue 9 (October 2016) - Lee, Shyong; Tang, Jung-Sung; Chu, Chun-Lin
Abstract Superplastic forming or gas forming is favorable method for the manufacture of sheet metal for making airplane skin panels. However, a major challenge in applying this method is controlling the thickness distribution in the formed product. Here, we explore a hot-bending-assisted process for gas forming of a deep trough with a complex shape for use in airplane wings. We propose the deliberate arrangement of wrinkles to achieve uniform thickness distribution. Because full-scale experiments are costly, sub-scale specimens are preferred for collecting experimental data. In linking sub-scale data to full-scale manufacturing, the size effect on wrinkle formation sites is important. The cause of the pre-form contour and larger-size specimen could be the greater variations in contour modes due to plastic buckling during the pre-forming stage.